Interest for difference in the contemporary world: ¿A possibility to think today the special education? (2010)
It shows the conceptual configuration of the idea of difference in the contemporary reports and their connection and incidence with the special education –considered as a discursive formation–. This notion of difference enables a field of crossing, composition and operation of forces –knowledges, subjects, practices– that make possible that definite objects or concepts achieve value to the present historical formation of the special education. It shows besides that these dynamics are giving ground to different understandings of some elements and establishing new connections between theoretical categories and subjectivities, generated by speeches and practices that are deploying a series of strategies and techniques that refer to subjects so dissimilar like: the educational, the schooling, the cultural, political and social, etc. Ways that at least see and read in a different way the special education in a contemporary world.